The Macau Roman Catholic Church and Its Limited Involvement in Civil Society - Tam, Yik-fai (Citizens of Two Kingdoms: Civil Society and Christian Religion in Greater China, 2021)
Abstract This chapter analyzes three constraints which affect the social involvement of the Macao Catholic Church, based on an inter-disciplinary method using social scientific and historical studies. First, addressing passiveness and conservativeness of the Portuguese Catholicism from which the Macao Catholic Church originated in relation to the Second Vatican Ecumenical Council. Second, showing the Macao Catholic Church demonstrates a comparatively traditional/conservative type of faith in contrast to the active and assertive roles of Roman Catholic Church in this-worldly affairs after Vatican II. Lastly, explaining the small size of Macao society poses a structural constraint on the civil involvement of the Church.
Keywords: Asian Studies; China; Practical Theology; Religion; Religion & Society; Religious Studies; Social Sciences; Sociology of Religion; Theology and World Christianity